The Marketing Strategy Affected the Competitiveness Capability of Running ODOP Business in Luang Prabang Province - phetsavong, somesack (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed To examine the level of importance of the marketing mix strategy among ODOP (One District One Product) businesses in Luang Prabang Province. To analyze the impact of the marketing mix strategy on the competitiveness of these businesses. A questionnaire was used as the primary data collection tool, targeting 83 ODOP entrepreneurs in the province. The data were analyzed using statistical software for descriptive statistical analysis. The results revealed that: The overall level of competitiveness among ODOP businesses in Luang Prabang Province is at a moderate level. Specifically, management and production were identified as high-level competitiveness factors, while finance and marketing were rated at a moderate level. The marketing mix strategy significantly influences the competitiveness of ODOP businesses. In particular, product strategy, pricing strategy, and distribution strategy were found to have a notable impact. These variables can serve as predictors of business competitiveness in the ODOP sector in Luang Prabang Province.